2013
DOI: 10.1016/j.wasman.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and microbial composition on odour in food waste composting

Abstract: Highlights► High odour emission from food waste compost was correlated to low pH. ► Microbes in high-odour samples included Lactic acid bacteria and Clostridia. ► For odour prevention, try high initial aeration rate and recycled compost as additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(67 citation statements)
references
References 28 publications
4
62
0
1
Order By: Relevance
“…The W1 presented acid pH and it is in accordance with Kumar et al (2010) and Sundberg (2013), who characterized food waste and verified pH values ranging from 3.8 to 6.5. The remaining residues resulted in pH close to neutral.…”
Section: Resultssupporting
confidence: 84%
“…The W1 presented acid pH and it is in accordance with Kumar et al (2010) and Sundberg (2013), who characterized food waste and verified pH values ranging from 3.8 to 6.5. The remaining residues resulted in pH close to neutral.…”
Section: Resultssupporting
confidence: 84%
“…Like these factors moisture impacts also on the physico-chemical properties [temperature, free air space (FAS), particle size, pH, C/N] of waste material to decompose during composting process (Kulcu and Yaldiz 2004). Several researchers also reported that optimum moisture content (55-60 %), C/N ratio (25)(26)(27)(28)(29)(30) and pH are the important factors for stabilization and maturation of compost (Sundberg et al 2013;Kumar et al 2010). Bulking agents are the fibrous with carbonaceous material, provide FAS and regulate water contents of waste to be composted because they modify the properties of waste during composting, due to high moisture, low C/N ratio and high density of waste.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proof that emission of odors from values of pH (21) The optimum pH of potting media would be different for different plants, but usually the desirable range was between 5.0 and 6.5 (22). This pH range of 5.1 to 6.0 was seen in the optimum range for growing media (23) who stated that the optimal range is from 5.2 to 7.3.…”
Section: Hydrogen Ion Level (Ph)mentioning
confidence: 99%
“…Early dehydration during composting usually comes from extreme low values of MC where it will stop the biological process, thus giving physically stable but biologically unstable composts (24). Several researchers also reported that optimum MC (55-60 %), C/N ratio (25)(26)(27)(28)(29)(30) and pH are the important factors for stabilization (25) and maturation of compost (21). Recent studies have shown that the municipal solid wastes generated in Malaysia contained a high percentage of organics (45-60%) with a MC of about 55% (26).…”
Section: Moisture Content (Mc) and Relative Humiditymentioning
confidence: 99%